2010
DOI: 10.1016/j.anbehav.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bonobo and chimpanzee tool use: evidence for a female bias in the Pan lineage

Abstract: Keywords: culture great ape neoteny Pan primate evolution sex difference tool use Chimpanzees, Pan troglodytes, are the most sophisticated tool-users among all nonhuman primates. From an evolutionary perspective, it is therefore puzzling that the tool use behaviour of their closest living primate relative, the bonobo, Pan paniscus, has been described as particularly poor. However, only a small number of bonobo groups have been studied in the wild and only over comparably short periods. Here, we show that capti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 49 publications
3
106
1
2
Order By: Relevance
“…Variation among great ape species in innovation and problem-solving biases illustrates this. Thus, bonobos bias their innovations, including those involving tool use, more toward solving social problems, chimpanzees more toward solving subsistence problems, and orangutans more toward enhancing physical comfort [50][51][52][53]. These divergent biases are found in the wild, but also in captivity, where conditions are uniform across the species concerned.…”
Section: Domain-specific or Domain-general Cognitive Abilities?mentioning
confidence: 96%
“…Variation among great ape species in innovation and problem-solving biases illustrates this. Thus, bonobos bias their innovations, including those involving tool use, more toward solving social problems, chimpanzees more toward solving subsistence problems, and orangutans more toward enhancing physical comfort [50][51][52][53]. These divergent biases are found in the wild, but also in captivity, where conditions are uniform across the species concerned.…”
Section: Domain-specific or Domain-general Cognitive Abilities?mentioning
confidence: 96%
“…Kanzi is able to produce stone flakes and selectively choose tools that are more useful than others [Schick et al, 1999]. These findings suggest that bonobos have the same understanding of the functional properties of tools as other great apes [Hermann et al, 2008] and a cognitive ability for toolrelated behaviours [Jordan, 1982;Gruber et al, 2010]. Gruber et al (2010) reported the nutcracking ability in the bonobos of Lola ya Bonobo sanctuary, but details of this complex tool-use behaviour have not yet been documented.…”
Section: Introductionmentioning
confidence: 95%
“…Despite the general absence of tool-use in the wild, bonobos in captivity demonstrate an equally diverse and highly complex repertoire of tool-use behaviours compared with captive chimpanzees [Jordan, 1982;Takeshita and Walraven, 1996;Gruber et al, 2010;Roffman et al, 2015]. The bonobo "Kanzi" is the best example illustrating this species' capability to develop highly skilled tool-making and tool-using behaviours [e.g., Toth et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative 542 studies of the physical and cognitive abilities of great apes have failed to explain the 543 paucity of tool use by bonobos. Within captive settings, bonobo tool use repertoires are as 544 large and diverse as chimpanzees (Gruber, Clay et al 2010). This is unlike gorillas, who 545 use tools for feeding but acquire the behaviour more slowly and perform it less frequently 546 than chimpanzees, suggesting a species difference in predisposition ( understanding of tool functional properties (Herrmann, Wobber et al 2008).…”
Section: Abundance Of Preferred Resources 296mentioning
confidence: 99%
“…use of tools, understanding of physical 555 causality) (Herrmann, Hare et al 2010). In a comparison of several captive groups, the 556 only major difference between chimpanzee and bonobo tool use was that bonobos of all 557 age and sex classes used tools in a play context (Gruber, Clay et al 2010). The propensity 558 of adult bonobos to engage in play is thought to reflect their neotenous nature, as well as 559 environmental conditions that afford leisure time and a behavioural preference for 560 certain types of social interaction.…”
Section: Abundance Of Preferred Resources 296mentioning
confidence: 99%